2010
DOI: 10.1144/0016-76492008-149
|View full text |Cite
|
Sign up to set email alerts
|

Seismic interpretation of Dinantian carbonate platforms in the Netherlands; implications for the palaeogeographical and structural development of the Northwest European Carboniferous Basin

Abstract: The Northwest European Carboniferous Basin is characterized by a series of carbonate platforms and intervening shale-dominated troughs during the Dinantian Sub-period. These structures have been mainly found along the margins of the basin. Here we present the results of an investigation of high-quality 3D seismic surveys, which has allowed the construction of a palaeogeographical and structural framework of the Dinantian Sub-period in the centre of the Northwest European Carboniferous Basin. Analysis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…From the Mid North Sea High northward, north-derived Dinantian clastics (Yoredale facies) are present instead of limestones (e.g. Besly, 2009;Kombrink et al, 2010;Milton-Worssell et al, 2010). The seismic interpretation by Milton-Worssell et al (2010) provides a clear image of the distribution of Dinantian highs and basins in this part of the North Sea.…”
Section: East Of the North Sea Central Graben (Eastern Domain)mentioning
confidence: 98%
See 2 more Smart Citations
“…From the Mid North Sea High northward, north-derived Dinantian clastics (Yoredale facies) are present instead of limestones (e.g. Besly, 2009;Kombrink et al, 2010;Milton-Worssell et al, 2010). The seismic interpretation by Milton-Worssell et al (2010) provides a clear image of the distribution of Dinantian highs and basins in this part of the North Sea.…”
Section: East Of the North Sea Central Graben (Eastern Domain)mentioning
confidence: 98%
“…Leeder, 1982Leeder, , 1992Glennie, 1986;Fraser and Gawthorpe, 1990;Johnston et al, 1996;Worthington and Walsh, 2011) where Cenozoic erosion has removed most of the cover, whereas the basins have largely escaped from later reactivation, notably in northern England. Dinantian extension has been recognised in the North Sea on the MNSH high and further south (Leeder and Hardman, 1990;Kombrink et al, 2010;Van Hulten, 2012) thanks to the presence of Dinantian limestone platforms on top of the horsts, providing sharp seismic contrasts in areas where the early Carboniferous is buried by younger strata. Recently, seismic mapping of the basement structure (Milton-Worssell et al, 2010;Ter Borgh et al, 2017a,b) revealed early Carboniferous horsts and grabens in Avalonia's northern corner in the North Sea, from the Iapetus suture to the MNSH.…”
Section: Early Carboniferous Basin and Fault Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the Early Carboniferous, the northern offshore area was a site of deltaic sedimentation derived from the North (Farne Group), while further south clastic sedimentation was much more limited. Here, carbonate platforms developed with intervening sedimentstarved basins (Carboniferous Limestone Group; Kombrink et al, 2010;Van Hulten & Poty, 2008). In Late Carboniferous (Namurian) times, siliciclastic sedimentation rates increased, leading to the burial of the carbonate platforms and the infilling of the deep basins.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Lauwerszee Trough already formed a basin in Early Carboniferous times when carbonate deposition occurred on both the Friesland and Groningen Platforms while the LT was probably a site of (distal) turbiditic and fine-grained sedimentation (Kombrink et al, 2010). It is bounded by two major fault systems in the west and east.…”
Section: Lauwerszee Trough (Lt)mentioning
confidence: 99%